KURIKULUM DEEP LEARNING SEBAGAI TRANSFORMASI INOVATIF MUTU PEMBELAJARAN - Haria Desti Nasution; Wirri Yanto (STKIP Pesisir Selatan, 2026)
This study analyzes the implementation of the deep learning curriculum as an innovative transformation to improve learning quality in educational institutions. The research was motivated by the shift toward active, reflective, contextual, and student-centered learning in 21st-century education. A qualitative case study approach was conducted at a secondary school implementing the Merdeka Curriculum. Participants included the principal, vice principal for curriculum affairs, teachers, and students selected through purposive sampling. Data were collected through semi-structured interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman interactive model. The findings revealed that the deep learning curriculum increased students’ engagement, motivation, collaboration, creativity, and critical thinking through meaningful and contextual learning activities. Teachers also played a greater role as facilitators in creating participatory and reflective classrooms. Nevertheless, several obstacles remained, particularly limited pedagogical competence among teachers and inadequate learning facilities. This study contributes to the development of innovative learning strategies for improving educational quality in schools and strengthening sustainable curriculum innovation in contemporary educational practices for institutional transformation and long-term instructional improvement across diverse settings.